Quality improvement through ergonomics methodology: Conceptual framework and an application - (:unkn) unknown (Inderscience Publishers, 2008)
This paper presents a conceptual framework of a methodology for Quality Improvement Through Ergonomics (QUITE) in a manufacturing context and an application of the proposed methodology in machine sewing task. Literature has demonstrated that quality performance in manufacturing can be improved via ergonomics interventions. The need for systematic methodologies to employ ergonomics with a quality improvement purpose formed the main motivation for development of QUITE methodology. Prerequisite organisational conditions for the application of QUITE methodology were set forth; the methodology can be applied in manufacturing organisations where human labour is significant, quality performance is systematically monitored and continuous improvement approach is prevalent. Three phases of QUITE methodology; planning, assessment and intervention were described in detail. Application in machine sewing task substantiated applicability of the methodology and resulted in a significant reduction of operator related defective products. It is considered that practitioners and researchers can benefit from QUITE methodology for quality improvement efforts in manufacturing context. © 2008, Inderscience Publishers.
Keywords: Ergonomics; Ergonomics intervention; Machine sewing; Manufacturing; Methodology; Quality improvement